Cortical control and performance monitoring of interrupting and redirecting movements. (27th February 2017) - Pouget, Pierre; Murthy, Aditya; Stuphorn, Veit
Abstract : Voluntary behaviour requires control mechanisms that ensure our ability to act independently of habitual and innate response tendencies. Electrophysiological experiments, using the stop-signal task in humans, monkeys and rats, have uncovered a core network of brain structures that is essential for response inhibition. This network is shared across mammals and seems to be conserved throughout their evolution. Recently, new research building on these earlier findings has started to investigate the interaction between response inhibition and other control mechanisms in the brain. Here we describe recent progress in three different areas: selectivity of movement inhibition across different motor systems, re-orientation of motor actions and action evaluation. This article is part of the themed issue 'Movement suppression: brain mechanisms for stopping and stillness'.